Nanosized ferroelectrics: Preparation, properties, and applications - Lustosa, Glauco M.M.M. [UNESP]; Teixeira, Guilhermina F. [UNESP]; Bastos, Wagner B. [UNESP]; Zanetti, Sonia M. [UNESP]; Perazolli, Leinig A. [UNESP]; Zaghete, Maria A. [UNESP] (Elsevier, 2018)
Top-down and bottom-up are two kinds of processes employed to obtain ferroelectric nanostructures. Top-down processes are physical methods involving the use of a bulk ferroelectric material to create coherently and continuously ordered nanosized structures (such as focused ion beam milling, nanoimprint lithography). On the other hand, bottom-up synthesis methods involve solution-based routes such as sol-gel, molten salt synthesis, solution-phase decomposition, and hydro/solvothermal synthesis, which lead to the production of different nanostructures (i.e., nanorings, nanowires, nanotubes) beginning at the atomic or molecular level.
Keywords: Chemical synthesis; Electrical properties; Ferroelectric nanostructure; Nanosized materials; Piezoresponse force microscopy